The Use of Video Recording and E-Sorogan Learning Method for Students with Special Needs In Microteaching - Saputri, Tiyas; Aquariza, Novi Rahmania; Wibowo, Rifky Adli Sulistyo (JPI (Jurnal Pendidikan Inklusi), 2024)
This study aims to report the 39 students’ perceptions (as pre-service foreign language teachers) on their experiences using video recording and e-Sorogan learning methods during teaching. One of them is a student with special needs diagnosed with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactive Disorder (ADHD). With these two methods (video recording and e-Sorogan learning methods), all students’ English teaching performance during microteaching and group discussions were recorded. After being recorded, all students’ English teaching materials and their English teaching performance role play videos were uploaded in e-Sorogan. Moreover, in e-Sorogan, all students gave comments on each other's teaching performance. The instrument used to collect the data of the study was a questionnaire survey through a google form. It consists of short answer questions available in the e-Sorogan classroom to obtain data from two open-ended questions on the students’ perceptions about video-recording and e-Sorogan learning methods. To collect the data, the questionnaire was distributed through the WhatsApp group. Data collected were analyzed qualitatively. The findings illustrated that the use of video recording and e-Sorogan learning methods in microteaching has both advantages and challenges for all students who take microteaching as the pre-service teachers, including the ASD and ADHD students. Keywords: Video Recording, e-Sorogan learning, Microteaching